Degradation Behavior of Carbon Fiber Reinforced Plastic (CFRP) in Microwave Irradiation - Nguyen Nguyen; Phuong Ngoc Diem; Susan A Roces; Florinda T Bacani; Masatoshi Kubouchi; Sakai Tetsuya; Piyachat Yimsiri (ASEAN Journal of Chemical Engineering, 2007)
Carbon fiber reinforced plastic (CFRP) composites are being used increasingly not only in strengthening structures of civil infrastructures and aerospace or automotive industries but also in many applications such as in medical fields or chemical plants. The present study relates to resin compositions having beneficial physical and mechanical properties, which may include improved resistance to delamination. This study focused on the different behaviors of CFRP composites when subjected to microwave irradiation. Based on the results of the 3-point bending test and SEM images, the delamination tendencies of breaking the CFRP under microwave were discussed. The results can be summarized as follows: (1) CFRP can be degraded under microwave irradiation; (2) two delamination tendency curves of CFRP by microwave irradiation were observed; (3) only the bending strength values of CFRP decreased with increasing microwave power and residence time; and, (4) the degradation of CFRP by microwave was limited.